2014
DOI: 10.1039/c4ra03669g
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun hybrid fibers with substantial filler contents formed through kinetically arrested phase separation in liquid jet

Abstract: This study reports polyhedral oligomeric silsesquioxane (POSS)-based hybrid fibers of architectural hierarchy and compositional heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…[9] SEM images for degraded 8:2 by mass PCL/m-iBuPOSS hybrid fibers are shown in Figure 6. The water/methanol was used to improve the surface wettability of the hybrid fibers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[9] SEM images for degraded 8:2 by mass PCL/m-iBuPOSS hybrid fibers are shown in Figure 6. The water/methanol was used to improve the surface wettability of the hybrid fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The enzymatic degradation clearly revealed the inner architecture of the crystalline PCL phase in the PCL/miBuPOSS fibers, which further extends the previous understanding of the fiber structure by using X-ray diffraction and X-ray photoelectron spectroscopy. [9] Upon rapid solvent evaporation, a significant amount of m-iBuPOSS nanocages were kinetically arrested (i.e., frozen) in the amorphous region of the PCL matrix in the dried outer layer of the liquid jet, while the inner phase was still drying. [9] The trapped m-iBuPOSS nanocages altered both the spacing and orientation of the PCL lamellae, giving rise to the highly porous, less-organized crystalline PCL phase, as observed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, various secondary nanostructured fibers have been produced by electrospinning techniques or the post‐treatment of electrospun fibers. Well‐documented research has shown interesting examples, such as nanoporous fibers, nanowrinkled fibers, and shish kebabs . Among these eye‐catching hierarchically structured electrospun fibers, nanofiber shish kebabs, for instance, have shown very promising applications for the guided growth of hydroxyapatite crystals .…”
Section: Introductionmentioning
confidence: 99%